Mesozoic intraplate deformation of the central North China Craton: Mechanism and tectonic setting. (1st May 2020) - Zhang, Jin; Qu, Junfeng; Zhang, Beihang; Zhao, Heng; Niu, Pengfei; Zhao, Shuo; Hui, Jie; Yun, Long; Nie, Fengjun; Wang, Yannan
Graphical abstract: Highlights: The central NCC experienced two-stage deformation during the Mesozoic. The Mesozoic deformation of the central NCC was controlled by preexisting basement fabrics. The Late Jurassic deformation was caused by the low-angle subduction of the Paleo-Pacific oceanic plate. Abstract: The North China Craton (NCC) is fundamentally characterized by Mesozoic intraplate deformation controlled by preexisting basement fabrics and far-field stress fields. In this study, a structural analysis of typical outcrops and representative sections was conducted to investigate the Mesozoic deformation in the central NCC. Our analysis indicates that this Mesozoic deformation is a typical example of thick-skinned tectonics and that the central NCC experienced two stages of deformation during this period. The first stage was driven by nearly east-west maximum compressional stress during the Late Jurassic, which led to the development of north-south-trending structures in the central NCC, such as the Lüliangshan range and Qinshui Basin. The second stage involved NNW-SSE maximum compressional stress during the Late Cretaceous, which resulted in the development of east-west-trending structures and the activation of large sinistral strike-slip faults, such as the Huoshan-Fushan fault. The key mechanism for the deformation during the Late Jurassic was the low-angle subduction of the Paleo-Pacific Plate beneath the NCC, which also laid the foundation for the later destruction of the craton during the Cretaceous. Moreover, a Late Cretaceous collision between the southeastern Eurasian continent and an unknown block or oceanic plateau may have resulted in the subsequent deformation of the NCC.